Integral Lipat Dua dalam Koordinat Kutub (Polar) - Radhiatul Asna, Radhia (Jurnal Pustaka Cendekia Pendidikan, 2023)
Double integrals are ordinary/single integrals where the result of the first integration must be reintegrated. This article will explain how to determine the value of the double integral in polar coordinates. The information collection method used is a literature study. By determining the double integral in polar coordinates, students can distinguish polar coordinates and Cartesian coordinates.